Implementasi Metode Sosiodrama Pada Mata Pelajaran Fikih Materi Zakat Di SMP IT Al Ikhwan Tanjung Morawa - Ahmad Dedi; Khairuddin Lubis; Ade Rahman Matondang (Journal of Innovative and Creativity, 2025)
The purpose of this study was to determine 1. Implementation of the sociodrama method in learning Islamic Religious Education on zakat material at SMP IT Al-Ikhwan Tanjung Morawa. 2. Student responses to the use of the sociodrama method in learning Islamic Religious Education on zakat material at SMP IT Al-Ikhwan Tanjung Morawa. 3. Supporting and inhibiting factors for the implementation of the sociodrama method in Islamic Religious subjects on zakat material at SMP IT Al-Ikhwan Tanjung Morawa. This type of research is qualitative. Research data were obtained from observation, interviews and documentation. The results of the study showed that: 1. Implementation of the sociodrama method in learning Islamic Religious Education on zakat material at SMP IT Al-Ikhwan Tanjung Morawa, especially in zakat material, gave positive results in helping students understand the concept of zakat more deeply. This method is effective because it involves students in real situations through role-playing, so that they not only learn theory, but also feel the impact of implementing zakat in everyday life. 2. Students' responses to the use of the sociodrama method in learning Islamic Religious Education on zakat material at SMP IT Al-Ikhwan Tanjung Morawa. are very positive. Students feel that this method makes learning more interesting and interactive, and helps them understand the concept of zakat more deeply. They find it easier to internalize the values of zakat through the roles played in sociodrama, so that the concept of zakat is not only a religious theory, but is also connected to practical applications in everyday life. 3. Supporting factors for the implementation of the sociodrama method in Islamic Religious subjects on zakat material at SMP IT Al-Ikhwan Tanjung Morawa include high student enthusiasm, full support from teachers, and a school environment that is conducive to interactive learning. While the inhibiting factors include time constraints in implementing sociodrama, which makes simulations unable to be carried out in depth.